Phosphogypsum-red mud composite foamed building block as well as preparation method and production equipment thereof

By using polymer foaming agents to achieve microporous foaming in composite foaming blocks of phosphogypsum and red mud, the problem of limited resource utilization of phosphogypsum and red mud is solved, and composite foaming blocks with good mechanical properties and low environmental impact are prepared.

CN119707524APending Publication Date: 2025-03-28SHENZHEN KEYU ENVIRONMENTAL PROTECTION IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510108237.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The resource utilization of phosphogypsum and red mud is limited, resulting in environmental pollution and land waste. The existing treatment methods such as landfill and low-volume cement concrete are not ideal for the application.

Method used

The preparation method of phosphogypsum-red mud composite foaming block is adopted to achieve microporous foaming through polymer foaming agent, and combined with the ratio of cement, water reducer and water, composite foaming blocks with good mechanical properties are prepared.

Benefits of technology

The efficient and comprehensive utilization of phosphogypsum and red mud is achieved, and the prepared phosphogypsum-red mud composite foamed block has light weight, high strength, low water absorption and good heat insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119707524A_ABST
    Figure CN119707524A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of waste utilization, in particular to an ardealite-red mud composite foamed building block and a preparation method and production equipment thereof. The phosphogypsum-red mud composite foamed building block provided by the invention is prepared from the following raw materials: phosphogypsum, red mud, cement, a polymer foaming agent, a water reducing agent and water. Microcellular foaming can be realized by adopting the polymer foaming agent, the performance of the building block is improved by co-doping with phosphogypsum, and the prepared phosphogypsum-red mud composite foamed building block has good mechanical properties, light weight, low water absorption (10-20%), good heat insulation performance and high red mud doping amount (up to 50-80%).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste utilization, and in particular to a phosphogypsum-red mud composite foamed building block and a preparation method and production equipment thereof. Background Art

[0002] Phosphogypsum is a solid waste produced in the wet phosphoric acid process, and its main component is calcium sulfate dihydrate. The composition of phosphogypsum is relatively complex. In addition to calcium sulfate, there are also incompletely decomposed phosphate ore, residual phosphoric acid, fluoride, acid insoluble matter, organic matter, etc. Among them, the presence of fluorine and organic matter has the greatest impact on the resource utilization of phosphogypsum. The random discharge and accumulation of phosphogypsum has seriously damaged the ecological environment, not only polluting groundwater resources, but also causing waste of land resources.

[0003] Red mud is an industrial solid waste discharged during the production of alumina. It is in the form of red powder because it contains a large amount of iron oxide. The output and composition of red mud vary depending on the grade of the ore, production method, and technical level, but it is estimated that 0.5 to 2 tons of red mud will be produced for every ton of alumina produced. There are three common alkaline methods for producing alumina in industry, namely sintering, Bayer process, and combined process. At present, more than 90% of the alumina and aluminum hydroxide produced in the world are obtained using the Bayer process.

[0004] If a large amount of phosphogypsum and red mud are not fully and effectively utilized, they can only be stored in large areas, which not only occupies a large amount of land, but also causes serious pollution to the environment. Although the current application of phosphogypsum involves many fields such as mine filling, building materials, and agriculture, its cumulative amount is still increasing year by year, and the pressure on the ecological environment remains severe. Due to its complex composition, it cannot completely replace natural gypsum in many application fields. Therefore, it is of great significance to develop new ways and methods for the resource utilization and large-scale utilization of phosphogypsum.

[0005] At present, the treatment method of red mud is basically landfill and dam storage. Such treatment methods are not only wasteful but also harmful to the environment. Although there are many studies on using red mud as an admixture in cement concrete materials, the red mud content is low (generally within 30wt%), and with the addition of red mud, the mechanical properties of the material decrease significantly, and the comprehensive utilization effect of red mud is not ideal. Summary of the invention

[0006] The object of the present invention is to provide a phosphogypsum-red mud composite foamed building block and a preparation method and production equipment thereof. The present invention not only realizes the comprehensive utilization of phosphogypsum and red mud, but also the prepared phosphogypsum-red mud composite foamed building block has light weight and high strength mechanical properties.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a phosphogypsum-red mud composite foaming building block, which comprises the following preparation raw materials: phosphogypsum, red mud, cement, a polymer foaming agent, a water reducing agent and water;

[0009] Taking the total mass of the phosphogypsum, red mud and cement as 100%, the mass of the phosphogypsum accounts for 10-30%, the mass of the red mud accounts for 50-80%, and the mass of the cement accounts for 10-40%;

[0010] The mass of the polymer foaming agent is 6-8% of the total mass of phosphogypsum, red mud and cement;

[0011] The mass of the water reducing agent is 0.1-0.2% of the total mass of phosphogypsum, red mud and cement;

[0012] The mass of the water is 20-30% of the total mass of phosphogypsum, red mud and cement;

[0013] The polymer foaming agent is composed of 0.1-1 wt% of a surfactant, 0.1-1 wt% of a foam stabilizer, 0.05-1 wt% of a reinforcing agent and the balance of water.

[0014] Preferably, the water reducer is a polycarboxylic acid-based high-efficiency water reducer.

[0015] Preferably, the cement is cement with a grade of PO42.5.

[0016] Preferably, the surfactant includes one or more of alkyl glycosides, saponins, fatty alcohol polyoxyethylene ethers, α-olefin sulfonates, fatty alcohol polyoxyethylene ether sulfates, fatty alcohol polyoxyethylene ether carboxylates, soapberry saponins, betulin, lupeol, γ-sitosterol, betaine, coconut oil amidoacetate, palmitamidopropyl ethylenediamine and oenothermide;

[0017] The foam stabilizer comprises one or more of nano kaolin, nano bentonite, nano silicon dioxide, nano attapulgite and nano montmorillonite;

[0018] The reinforcing agent includes cellulose and / or cellulose derivatives.

[0019] Preferably, the median particle size of the red mud is 2 to 25 μm.

[0020] Preferably, the 28-day compressive strength of the phosphogypsum-red mud composite foamed building block is 1 to 7 MPa.

[0021] The present invention provides a method for preparing the phosphogypsum-red mud composite foamed building block described in the above scheme, comprising the following steps:

[0022] Mixing water and a water reducing agent to obtain a mixed liquid;

[0023] The mixed liquid is mixed with phosphogypsum, red mud and cement to obtain a slurry;

[0024] foaming a polymer foaming agent to obtain foamed foam;

[0025] Adding the foamed foam into the slurry and casting it into shape to obtain a green sheet;

[0026] The green sheet is cured to obtain the phosphogypsum-red mud composite foamed building block.

[0027] Preferably, the fluidity of the slurry is 20 to 22 cm.

[0028] Preferably, the curing temperature is 23±5° C., the relative humidity is 50-90%, and the curing time is 14-28 days.

[0029] The present invention provides production equipment for implementing the preparation method described in the above scheme, including: a water weighing component 1, a red mud silo 2, a red mud crusher 3, a cement tank 4, a phosphogypsum silo 5, a feeder 6, a solid material weighing component 7, a mixer 8, a polymer foaming agent configuration component 9, a foaming agent weighing component 10, a foaming machine 11, a casting mold 12 and a curing room 13.

[0030] The invention provides a phosphogypsum-red mud composite foaming building block, comprising the following preparation raw materials: phosphogypsum, red mud, cement, a polymer foaming agent, a water reducing agent and water; taking the total mass of the phosphogypsum, red mud and cement as 100%, the mass of the phosphogypsum accounts for 10-30%, the mass of the red mud accounts for 50-80%, and the mass of the cement accounts for 10-40%; the mass of the polymer foaming agent is 6-8% of the total mass of the phosphogypsum, red mud and cement; the mass of the water reducing agent is 0.1-0.2% of the total mass of the phosphogypsum, red mud and cement; the mass of the water is 20-30% of the total mass of the phosphogypsum, red mud and cement; the polymer foaming agent consists of 0.1-1wt% of a surfactant, 0.1-1wt% of a foam stabilizer, 0.05-1wt% of an enhancer and the remainder of water. The present invention adopts a polymer solid foaming agent to achieve microporous foaming, and improves the block performance by compounding with phosphogypsum. The prepared phosphogypsum-red mud composite foamed building block has good mechanical properties, and the red mud content is high, reaching 50-80%.

[0031] The results of the examples show that the composite foamed building blocks prepared by using phosphogypsum and red mud have good mechanical properties (28-day compressive strength of 1-7 MPa), light weight (dry density of 900-1000 kg / m 3 ), low water absorption (10-20%), and good thermal insulation performance (thermal conductivity <0.3W / (m·K)). BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a flow chart of the preparation of phosphogypsum-red mud composite foamed building blocks in the embodiment;

[0033] Figure 2 It is a schematic diagram of the composition of the production equipment of phosphogypsum-red mud composite foamed building blocks;

[0034] Figure 3 This is a real photo of the phosphogypsum-red mud foamed building block prepared in Example 1;

[0035] Figure 4 This is a real photo of the phosphogypsum-red mud foamed building block prepared in Example 2;

[0036] Figure 5 This is a physical photo of the phosphogypsum-red mud foamed building block prepared in Example 3. DETAILED DESCRIPTION

[0037] The invention provides a phosphogypsum-red mud composite foaming building block, which comprises the following preparation raw materials: phosphogypsum, red mud, cement, a polymer foaming agent, a water reducing agent and water.

[0038] In the present invention, taking the total mass of the phosphogypsum, red mud and cement as 100%, the mass of the phosphogypsum accounts for 10-30%, the mass of the red mud accounts for 50-80%, and the mass of the cement accounts for 10-40%.

[0039] In a specific embodiment, the mass proportion of the phosphogypsum can be 10%, 15%, 20%, 25% or 30%; the mass proportion of the red mud can be 50%, 55%, 60%, 65%, 70%, 75% or 80%; the mass proportion of the cement can be 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0040] The present invention has no special requirements on the source of the phosphogypsum, and any phosphogypsum from sources well known in the art can be used.

[0041] In the present invention, the red mud is preferably red mud obtained by the Bayer process; the median particle size of the red mud is preferably 2 to 25 μm.

[0042] In the present invention, the cement is preferably cement with a grade of P·O42.5.

[0043] In the present invention, the mass of the polymer solid foaming agent is 6-8% of the total mass of phosphogypsum, red mud and cement, and in a specific embodiment it can be 6%, 7% or 8%.

[0044] In the present invention, the polymer foaming agent is a self-made foaming agent, and its components are: 0.1-1wt% surfactant, 0.1-1wt% foam stabilizer, 0.05-1wt% enhancer, and the balance is water.

[0045] In the present invention, the surfactant preferably includes one or more of alkyl glycosides, saponins, fatty alcohol polyoxyethylene ethers, α-olefin sulfonates, fatty alcohol polyoxyethylene ether sulfates, fatty alcohol polyoxyethylene ether carboxylates, soapberry saponin, betulin, lupeol, γ-sitosterol, betaine, coconut oil amide acetate, palmitamide propyl ethylenediamine and oenothecinamide; the foam stabilizer preferably includes one or more of nano kaolin, nano bentonite, nano silica, nano attapulgite and nano montmorillonite; the enhancer preferably includes cellulose and / or cellulose derivatives.

[0046] In a specific embodiment, the content of alkyl glycoside surfactant in the foaming agent can be 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%; the content of nano-silicon dioxide in the foaming agent can be 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%; the content of methyl cellulose in the foaming agent can be 0.05wt%, 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%.

[0047] The present invention adopts a polymer foaming agent to achieve microporous foaming, reduce the mass of the foamed building block, and ensure its strength at the same time.

[0048] In the present invention, the mass of the water reducer is 0.1-0.2% of the total mass of phosphogypsum, red mud and cement; in a specific embodiment, it can be 0.1%, 0.15% or 2%. In the present invention, the water reducer is preferably a polycarboxylic acid-based high-efficiency water reducer. The polycarboxylic acid-based high-efficiency water reducer used in the present invention has high water reduction efficiency, low dosage and is easy to use.

[0049] In the present invention, the mass of the water is 20-30% of the total mass of the phosphogypsum, red mud and cement; in a specific embodiment, it can be 20%, 22%, 25% or 30%.

[0050] In the present invention, the 28-day compressive strength of the phosphogypsum-red mud composite foamed building block is preferably 1-7 MPa, more preferably 5-6 MPa; the dry density is preferably 900-1000 kg / m 3 ; The water absorption rate is preferably 10-20%; The thermal conductivity is preferably <0.3W / (m·K), and more preferably 0.2-0.3W / (m·K).

[0051] The present invention provides a method for preparing the phosphogypsum-red mud composite foamed building block described in the above scheme, comprising the following steps:

[0052] Mixing water and a water reducing agent to obtain a mixed liquid;

[0053] The mixed liquid is mixed with phosphogypsum, red mud and cement to obtain a slurry;

[0054] foaming a polymer foaming agent to obtain foamed foam;

[0055] Adding the foamed foam into the slurry and casting it into shape to obtain a green sheet;

[0056] The green sheet is cured to obtain the phosphogypsum-red mud composite foamed building block.

[0057] The present invention mixes water and a water reducing agent to obtain a mixed liquid.

[0058] In the present invention, the mixing is preferably carried out in a stirrer; the mixing time is preferably 1 to 3 minutes.

[0059] After obtaining the mixed liquid, the present invention mixes the mixed liquid with phosphogypsum, red mud and cement to obtain slurry.

[0060] Before the mixing, the red mud is preferably crushed in the present invention.

[0061] In the present invention, phosphogypsum, red mud and cement are preferably added to the mixed liquid for mixing. In the present invention, the mixing is preferably carried out in a mixer; and the mixing time is preferably 3 to 5 minutes.

[0062] In the present invention, the fluidity of the slurry is preferably 20 to 22 cm.

[0063] The invention foams a polymer foaming agent to obtain foamed foam.

[0064] In the present invention, the foaming is preferably carried out in a foaming machine. The present invention has no special requirements for the foaming process.

[0065] After obtaining the slurry and the foaming foam, the present invention adds the foaming foam into the slurry, and then casts and shapes the slurry to obtain a green sheet.

[0066] After the foaming foam is added, the present invention is preferably stirred for 3 to 5 minutes before pouring into shape.

[0067] In the present invention, the casting is preferably carried out in a casting mold.

[0068] After obtaining the cast billet, the present invention cures the green billet to obtain the phosphogypsum-red mud composite foamed building block.

[0069] In the present invention, the curing is preferably carried out in a curing room, the curing temperature is preferably 23±5°C, the relative humidity is preferably 50-90%, and the curing time is preferably 14-28 days. In a specific embodiment, the relative humidity of the curing can be 50%, 60%, 70%, 80% or 90%; the curing time can be 14 days, 18 days, 20 days, 24 days or 28 days.

[0070] like Figure 2 As shown, the present invention provides a production equipment for implementing the preparation method described in the above scheme, including: a water weighing component 1, a red mud silo 2, a red mud crusher 3, a cement tank 4, a phosphogypsum silo 5, a feeder 6, a solid material weighing component 7, a mixer 8, a polymer foaming agent configuration component 9, a foaming agent weighing component 10, a foaming machine 11, a casting mold 12 and a curing room 13.

[0071] In the present invention, the water weighing component 1 is used to add water required for production according to the proportion; the red mud silo 2 is used to store red mud; the red mud crusher 3 is used to crush the red mud raw materials; the cement tank 4 is used to store cement; the phosphogypsum silo 5 is used to store phosphogypsum; the feeder 6 and the solid material weighing component 7 are used to add the solid raw materials required for production (i.e., red mud, cement and phosphogypsum) according to the proportion.

[0072] In the present invention, the polymer foaming agent configuration component 9, the foaming agent weighing component 10 and the foaming machine 11 are respectively used to prepare the required foaming agent and weigh the required foaming agent according to the ratio, and then the foam is beaten into the mixer 8 through the foaming machine 11.

[0073] In the present invention, the mixer 8 is used to first stir water and a water reducing agent, then add solid raw materials (red mud, phosphogypsum and cement) to obtain a slurry by stirring, and finally add foaming foam to obtain a phosphogypsum-red mud composite foaming slurry by stirring.

[0074] The present invention pours the phosphogypsum-red mud composite foaming slurry into a casting mold 12, performs curing in a curing room 13, and obtains the phosphogypsum-red mud composite foaming building block after demolding.

[0075] The phosphogypsum-red mud composite foamed building block and its preparation method and production equipment provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0076] Example 1

[0077] The material ratio is shown in Table 1, and the preparation steps refer to Figure 1 , as follows:

[0078] After weighing the water using the water weighing assembly 1, the water and the polycarboxylic acid-based high-efficiency water reducing agent are added to the mixer 8 and stirred for 2 minutes;

[0079] After the red mud is crushed into solid powder (particle size 2-25 μm) by the red mud crusher 3, the crushed red mud, cement (labeled as P·O 42.5) and phosphogypsum are weighed by the solid material weighing component 7 according to the mixing ratio and added into the mixer 8, and stirred for 3-5 minutes to make them fully mixed and uniform, so as to obtain a slurry material.

[0080] Add the polymer foaming agent to the foaming machine 11 according to the mixing ratio, then use the foaming machine to beat the foam into the mixer 8, stir for 3 to 5 minutes to make the foam and slurry mix evenly, and then cast in the casting mold 12 to obtain a blank;

[0081] The green sheet is placed in a curing room 13 for curing treatment. The curing conditions are a curing temperature of 23±5° C., a humidity of 90%, and a curing time of 28 days to obtain a phosphogypsum-red mud foamed block (such as Figure 3 shown).

[0082] Table 1 Material ratio of Example 1

[0083] Phosphogypsum Red Mud cement Foaming agent Water reducing agent water 10% 60% 30% 8% 0.1% 20%

[0084] Note: In Table 1, the amount of phosphogypsum, red mud and cement is calculated based on the mass of solid powder materials, and the amount of foaming agent, water reducing agent and water is also calculated based on the mass of solid powder materials. The same is true for the following Tables 3 and 5.

[0085] Performance Test:

[0086] The performance test of the phosphogypsum-red mud composite foamed building block of Example 1 was carried out, and the test method referred to the relevant provisions in the national standard "Test Methods for Foamed Concrete and Products GB / T 43487-2023".

[0087] Compressive strength test method:

[0088] The specimen size is 100mm×100mm×100mm, and the number is 6. The specimen pressure area A is calculated, and the specimen is placed on the pressure plate of the testing machine, so that the center of the pressure plate of the testing machine coincides with the center of the specimen. The testing machine is started, and the load is applied until the specimen is destroyed. The failure load P is recorded, accurate to 10N, and the loading speed meets the requirements of the specification. The specimen compressive strength f = P / A, accurate to 0.01MPa.

[0089] Dry density test method:

[0090] The size of the specimen is 100mm×100mm×100mm, and there are 6 specimens. The size of the specimen is measured to an accuracy of 0.1mm, and the volume V of the specimen is calculated. The specimen is placed in an electric blast drying oven, and the temperature is raised to (105±2)℃ at a rate of 10℃ / h. It is dried to a constant mass at this temperature, and then moved to a dryer to cool to room temperature. The cooling time is not less than 24h. The criterion for constant mass is that the rate of change of the mass of the specimen measured twice at a constant temperature for 180min is less than 0.2%. Weigh the mass m of the specimen after drying to an accuracy of 0.1g. The dry density of the specimen is ρ=m / V×106, accurate to 1kg / m 3 .

[0091] Water absorption test method:

[0092] The size of the specimen is 100mm×100mm×100mm, and the number is 6. The size of the test specimen is tested with an accuracy of 0.1mm. The volume V of the specimen is calculated. The specimen is placed on the grid at the bottom of the constant temperature water tank. The distance between the specimen and the surrounding and the specimen should not be less than 25mm. Then, another grid is placed on the upper surface of the specimen and a pressure block is added. Water with a temperature of (20±2)℃ is added to the water tank three times. The first time, water is added to 1 / 3 of the specimen height and kept for 24h. The second time, water is added to 2 / 3 of the specimen height. After 24h, the third time, water is added to be more than 25mm higher than the specimen and kept for 120h. The specimen is taken out of the water and placed on a wire mesh rack to drip water for 1min. The surface water is wiped off with a wrung wet cloth. The mass m of each specimen in the saturated dry state is weighed. 1 , accurate to 0.1g, dry the specimen to a constant mass, then move it to a drying room and cool it to room temperature, and weigh its mass m after drying 2 The water absorption rate of the specimen is W = (m 1 -m 2 ) / m 2 ×100%, accurate to 0.1%.

[0093] Thermal conductivity test method:

[0094] The specimen size is 300mm×300mm×30mm, and the quantity is 2. The specimen size is tested. The specimen is dried to a constant mass. The thermal conductivity of the specimen is tested using a thermal conductivity meter according to the specification GB / T 10294. The result is accurate to 0.001W / (m·K).

[0095] The test results are shown in Table 2.

[0096] Table 2 Performance of Example 1 Phosphogypsum-red mud composite foamed building blocks

[0097] 28-day compressive strength (MPa) <![CDATA[Dry density (kg / m 3 )]]> Water absorption (%) Thermal conductivity (W / (m·K)) 6.42 983 12.6 0.228

[0098] Example 2

[0099] Preparation of phosphogypsum-red mud foamed blocks (such as Figure 4 As shown), the material ratio is shown in Table 3;

[0100] The preparation method is the same as Example 1.

[0101] The performance test of the phosphogypsum-red mud composite foamed building block of Example 2 was carried out with reference to the test method of Example 1. The test results are shown in Table 4.

[0102] Table 3 Material ratio of Example 2

[0103] Phosphogypsum Red Mud cement Foaming agent Water reducing agent water 20% 70% 10% 8% 0.1% 20%

[0104] Table 4 Performance of Example 2 Phosphogypsum-red mud composite foamed building blocks

[0105] 28-day compressive strength (MPa) <![CDATA[Dry density (kg / m 3 )]]> Water absorption (%) Thermal conductivity (W / (m·K)) 5.92 966 14.3 0.219

[0106] Example 3

[0107] Preparation of phosphogypsum-red mud foamed blocks (such as Figure 5 As shown), the material ratio is shown in Table 5;

[0108] The preparation method is the same as Example 1.

[0109] The performance test of the phosphogypsum-red mud composite foamed building block of Example 2 was carried out with reference to the test method of Example 1. The test results are shown in Table 6.

[0110] Table 5 Material ratio of Example 3

[0111] Phosphogypsum Red Mud cement Foaming agent Water reducing agent water 30% 60% 10% 8% 0.1% 20%

[0112] Table 6 Performance of Example 3 phosphogypsum-red mud composite foamed building blocks

[0113] 28-day compressive strength (MPa) <![CDATA[Dry density (kg / m 3 )]]> Water absorption (%) Thermal conductivity (W / (m·K)) 5.14 1007 18.6 0.249

[0114] It can be seen from the above embodiments that the composite foamed building block prepared by using phosphogypsum and red mud in the present invention has good mechanical properties, light weight, low water absorption, and good thermal insulation performance.

[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A phosphogypsum-red mud composite foamed building block, characterized in that: The preparation raw materials include: phosphogypsum, red mud, cement, polymer foaming agent, water reducing agent and water; Taking the total mass of the phosphogypsum, red mud and cement as 100%, the mass of the phosphogypsum accounts for 10-30%, the mass of the red mud accounts for 50-80%, and the mass of the cement accounts for 10-40%; The mass of the polymer foaming agent is 6-8% of the total mass of phosphogypsum, red mud and cement; The mass of the water reducing agent is 0.1-0.2% of the total mass of phosphogypsum, red mud and cement; The mass of the water is 20-30% of the total mass of phosphogypsum, red mud and cement; The polymer foaming agent is composed of 0.1-1 wt% of a surfactant, 0.1-1 wt% of a foam stabilizer, 0.05-1 wt% of a reinforcing agent and the balance of water.

2. The phosphogypsum-red mud composite foamed building block according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent.

3. The phosphogypsum-red mud composite foamed building block according to claim 1, characterized in that: The cement is cement with a grade of PO42.

5.

4. The phosphogypsum-red mud composite foamed building block according to claim 1, characterized in that: The surfactant includes one or more of alkyl glycosides, saponins, fatty alcohol polyoxyethylene ethers, α-olefin sulfonates, fatty alcohol polyoxyethylene ether sulfates, fatty alcohol polyoxyethylene ether carboxylates, soapberry saponins, betulin, lupeol, γ-sitosterol, betaine, coconut oil amide acetate, palmitamidopropyl ethylenediamine and oenothermide; The foam stabilizer comprises one or more of nano kaolin, nano bentonite, nano silicon dioxide, nano attapulgite and nano montmorillonite; The reinforcing agent includes cellulose and / or cellulose derivatives.

5. The phosphogypsum-red mud composite foamed building block according to claim 1, characterized in that: The median particle size of the red mud is 2 to 25 μm.

6. The phosphogypsum-red mud composite foamed building block according to any one of claims 1 to 5, characterized in that: The 28-day compressive strength of the phosphogypsum-red mud composite foamed building block is 1-7 MPa.

7. The method for preparing the phosphogypsum-red mud composite foamed building block according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mixing water and a water reducing agent to obtain a mixed liquid; The mixed liquid is mixed with phosphogypsum, red mud and cement to obtain a slurry; foaming a polymer foaming agent to obtain foamed foam; Adding the foamed foam into the slurry and casting it into shape to obtain a green sheet; The green sheet is cured to obtain the phosphogypsum-red mud composite foamed building block.

8. The preparation method according to claim 7, characterized in that: The fluidity of the slurry is 20-22 cm.

9. The preparation method according to claim 7, characterized in that: The curing temperature is 23±5° C., the relative humidity is 50-90%, and the curing time is 14-28 days.

10. A production equipment for implementing the preparation method according to any one of claims 7 to 9, characterized in that: include: A water weighing component (1), a red mud silo (2), a red mud crusher (3), a cement tank (4), a phosphogypsum silo (5), a feeder (6), a solid material weighing component (7), a mixer (8), a polymer foaming agent configuration component (9), a foaming agent weighing component (10), a foaming machine (11), a casting mold (12) and a curing room (13).